319 Effects of omega-3 fatty acid supplementation on atopic dermatitis. (25th January 2023) - Abdenour, Alyssa M; Shareef, Sarah J; Kreuser, Kaitlin; Ashack, Kurt
Abstract: Oral supplements are commonly used by patients to enhance skin health for aesthetic purposes and in response to cutaneous disorders. Currently, the Food and Drug Administration (FDA) is not authorized to approve the efficacy or safety of dietary supplements prior to public marketing. Therefore, evidence-based medicine is needed for dermatologists to better counsel patients regarding oral supplementation. Physicians must take this into consideration while treating patients with chronic conditions, such as atopic dermatitis (AD). AD is the most common cutaneous inflammatory disease affecting individuals from infancy through adulthood. Prevention and management are focused on avoiding environmental triggers, daily skin care with emollients and/or topical steroids, and decreasing systemic inflammation. Patients with AD use various treatment options and over-the-counter supplements throughout their lifetime. Interestingly, omega-3 fatty acids (O3FA) are marketed for their anti-inflammatory effects and have been widely studied to understand health benefits. To our knowledge, the effects of oral supplementation of O3FA (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]) for AD are not summarized in the literature. Thus, this study was conducted to examine O3FA's impact on AD and ultimately, to determine if supplementation is an effective therapy for the prevention and/or treatment of AD. A comprehensive electronic search with EPA and DHA for atopic dermatitis in PubMed/MEDLINE, Cochrane Central, Embase, and Google Scholar yielded 45 articles. Duplicate, non-English articles and irrelevant articles were excluded. These parameters resulted in 38 articles being excluded as they did not meet study qualifications. Therefore, seven articles are included in this review. Of the included articles, 2/7 studies discussed an improvement in skin inflammation with O3FA supplementation, while 5/7 did not find a significant difference in the prevention of allergic disease. On the other hand, one trial resulted in a significant decline in the prevalence of eczema and another indicated significant clinical improvement compared to baseline, but not in comparison to the placebo. O3FA supplementation is not effective in preventing allergic symptoms, but may decrease the prevalence of AD and provide clinical improvement. Further evaluation is needed to characterize the efficacy of O3FA supplementation in the prevention and treatment of AD.